Characterization and screening of urease activity of ureolytic bacteria from landfills soil in Banda Aceh, Indonesia - LENNI FITRI; TEUKU BUDI AULIA; AMIR FAUZI; GALIH AHMAD KAMIL (Society for Indonesian Biodiversity, 2023)
Abstract. Fitri L, Aulia TB, Fauzi A, Kamil GA. 2023. Characterization and screening of urease activity of ureolytic bacteria from landfills soil in Banda Aceh, Indonesia. Biodiversitas 24: 910-915. Ureolytic bacteria are capable of producing the calcium carbonate precipitating enzyme urease. Ureolytic bacteria degrade urease into ammonia and carbon dioxide. Ureolytic bacteria can be applied in the bio-grouting technique and concrete mixtures. This study aimed to isolate and characterize ureolytic bacteria isolates, then determine the calcium carbonate precipitation potential of ureolytic bacteria isolates from landfill soil at Gampong Jawa, Banda Aceh, Indonesia. This research successfully isolated twenty-four bacterial isolates from the Gampong Jawa landfills, and ten of these isolates were confirmed to produce the urease enzyme positively. Isolates with codes BTPA-3, BTPA-6, BTPA-7, BTPA-8, BTPA-9, BTPA-15, BTPA-20, BTPA-22, BTPA-23, and BTPA-24 were able to precipitate calcium carbonate in the amounts of 1.49, 1.78, 1.71, 1.70, 1.82, 1.80, 1.32, 1.54, and 1.70 g, respectively. BTPA-3, BTPA-6, BTPA-7, BTPA-8, BTPA-9, BTPA-23, and BTPA-24 were identified as members of the genus Bacillus; BTPA-20 was as a member of the genus Staphylococcus; and BTPA-15 and BTPA-22 were members of the genus Solibacillus. This research data is new information about the potential of bacteria from the Gampong Jawa landfill, which can determine the calcium carbonate precipitation. The research also revealed that the ureolytic bacterial isolates produced could be further improved and utilized in concrete mixtures.